The Effect of Awarding Incentives Toward Employee Productivity at CV. Abdul Fishing - Alfi Maghfuriyah; Udriyah; Marini Fitriyani (Lead Journal of Economy and Administration, 2023)
The purpose of this study is to ascertain how incentives at CV. Abdul Fishing in Sukabumi Regency affect worker productivity. This study's design, which takes a quantitative approach, combines associative and descriptive research techniques. The sample used in this study consisted of 70 respondents who were drawn from the whole workforce at CV. Abdul Fishing in Sukabumi Regency using complete sampling or census methodologies. To test the analysis in this study, correlation analysis, analysis of the coefficient of determination, and simple linear regression were used in conjunction with instrument validity tests, instrument reliability tests, descriptive analysis, and statistical analysis tests for relationship analysis and influence. According to the findings of previous research, incentives have a positive effect on employee work productivity at CV. Abdul fishing in the Sukabumi Regency. The magnitude of the effect of incentives on employee productivity is 54.1%, with the remaining 45.9% influenced by variables other than incentive-giving variables such as leadership style, discipline, motivation, work morale, work experience, and others.